2020
DOI: 10.21203/rs.2.23129/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of ED95 of Butorphanol with Sufentanil for Gastrointestinal Endoscopy Sedation: a randomized controlled trial

Abstract: Background: Butorphanol, a synthetic opioid partial agonist analgesic, has been widely used for the control of perioperative pain. However, the ideal dose and availability of butorphanol for gastrointestinal (GI) endoscopy are not well known. The aim of this study was to evaluated the 95% effective dose (ED95) of butorphanol and sufentanil in GI endoscopy and compared their clinical efficacy, especially the recovery time.Methods: The study was divided into two parts. For the first part, voluntary patients who … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…[19] Butorphanol is a derivative of morphinan, which partially antagonizes α-opioid receptors and reduces the incidence of nausea, vomiting, and other postoperative side effects. [20] In a randomized controlled trial of gastrointestinal endoscopic analgesia, [21] butorphanol reduced postoperative nausea and vomiting, possibly due to reduced gastrointestinal motility and smooth muscle spasm, which in turn reduced the incidence of vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Butorphanol is a derivative of morphinan, which partially antagonizes α-opioid receptors and reduces the incidence of nausea, vomiting, and other postoperative side effects. [20] In a randomized controlled trial of gastrointestinal endoscopic analgesia, [21] butorphanol reduced postoperative nausea and vomiting, possibly due to reduced gastrointestinal motility and smooth muscle spasm, which in turn reduced the incidence of vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, some of these studies added a confirmatory stage enrolling n = 30 to 100 patients and treating them at the estimated higher percentile. 37,40 While some studies reported results that corroborate the off-target estimate, a better use of the additional sample might have been to follow upon the classical up-and-down design with a high-target up-and-down design, using the first stage to refine the dose spacing as suggested earlier in this section.…”
Section: Estimating Two Distinct Target Dosesmentioning
confidence: 99%
“…, estimating the ED95 using ED50-finding up-and-down design data, a practice that has become prevalent in recent anesthesiology studies). 28,35–40 Such estimates are likely biased in the direction of the ED50 ( i.e. , downward).…”
Section: Up-and-down Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be duo to: 1) dexamethasone being regularly used in premedication along with intra-operative 5HT3 antagonists; 2) su cient anti-emetic (normally 9 mg ondensteron) accompanying opioid analgetics (butorphanol ± fentanyl at much lower dosage) during postoperative patient-controlled analgesia in our hospital. Butorphanol is less likely to cause PONV [24]. Multivariate logistic regression analysis with factors associated with PONV in entire cohort.…”
mentioning
confidence: 99%